Gender-Based Compliments Used by Judges in America’s Got Talent 2019 - Puji Arifti Hanifah; Leni Marlina (Universitas Negeri Padang, 2022)
Humans use a variety of communication methods to convey their messages, including apologies, requests, complaints, and compliments. Different communication traits apply to men and women. There are variations in their methods of compliment expression due to the differences in their communication styles. Culture and language are inseparable. The compliment is inextricably linked to culture as a component of language. Their cultural background has a big impact on how they complimented people. The study's analysis of the judges' complimenting styles during the 2019 season of America's Got Talent is its main focus. The study examines the subject, methods, purposes, and syntactic structure of compliments. A qualitative descriptive methodology used in this study. The information was the praise the judges gave to each finalist in their comments. 72 compliments were gathered from America's Got Talent. The results indicate that male judges were more likely to give compliments than female judges. Regarding compliments, the performances of the finalists received more compliments, from male and female judges than from them on other topics. In their delivery of compliments, male judges tended to employ explicit techniques than female judges, but females were more likely to use implicit techniques. In the context of compliments, male judges typically use them to show admiration or approval for someone's work, appearance, or taste, whereas female judges typically use them to replace thanks, greetings, congratulations, and apologies. Finally, judges who were male or female were more likely to compliment others using the phrase PRO is (really) (a) ADJ NP and PRO is/are/was/were more often when making compliments. They are more likely to use impersonal compliments. In conclusion due to the topic, techniques, purpose, and grammatical structure of compliments, there are some variances and similarities in the praising behavior of men and women.